Pythia8 MC Tuning Validation Using the Professor2 Package - Ghumaryan, Hazaravard M. (Mathematical Problems of Computer Science, 2024)
This article presents a method for multi-parameter, simultaneous tuning of the Monte Carlo event generator. It is validated on the Pythia8 Monte Carlo event generator widely used in High Energy Physics (HEP). The obtained results show that the method can be used to constrain the free parameters of phenomenological models while properly taking into account the correlations existing among the parameters.